2021
DOI: 10.1016/j.dsx.2021.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Analysis for fear of COVID-19 Scale (FCV-19S) and its association with depression in patients with diabetes: A cross sectional study from a Tertiary Care Centre in Karachi, Pakistan

Abstract: Background and aims To assess the psychometric properties of the Fear of COVID-19 (FCV–19S) scale and to determine its associated factors among the Pakistani patients with diabetes. Methods This observational study was conducted in 24-h helpline service, a department of Baqai Institute of Diabetology and Endocrinology (BIDE). Study duration was from August to September 2020. The target population was registered adult patients with type 2 diabetes aged >16 years. Baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
4
14
1
Order By: Relevance
“…As illustrated in “ Fig 3A” , the fear score was higher in women than men. Our findings are in line with findings from Basit et al [ 19 ] who assessed the fear of Covid 19 among a subgroup of Pakistani patients with type 2 diabetes. However, this result is in contrast to the finding of Ahorsu et al, who has developed the fear of Covid 19 scale in the general Iranian population.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As illustrated in “ Fig 3A” , the fear score was higher in women than men. Our findings are in line with findings from Basit et al [ 19 ] who assessed the fear of Covid 19 among a subgroup of Pakistani patients with type 2 diabetes. However, this result is in contrast to the finding of Ahorsu et al, who has developed the fear of Covid 19 scale in the general Iranian population.…”
Section: Discussionsupporting
confidence: 93%
“…The finding is reasonable as older age was launched as a risk factor for serious disease and bad outcome early in the pandemic. The finding is however in conflict with findings from Basit et al, who found no association between fear scores and age [19], and findings from Lee et al, who assessed the coronavirus anxiety in healthy Turkish people. They found that younger people were more afraid of Covid 19 than older people [20].…”
Section: Plos Onecontrasting
confidence: 96%
See 1 more Smart Citation
“…A higher perception of risk of contagion tends to lead to better preventive actions and better disease control [ 47 ]. Moreover, the belief about the likelihood of contracting COVID-19 is even more important if we consider that just over 50% of diabetic patients are afraid of COVID-19 [ 20 ]. In general, all items of the five-item model present adequate discrimination parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Given this scenario, it is important to have valid and reliable measures to determine the psychological impact of COVID-19 in patients with diabetes. However, few instruments have been developed and validated for this population, with only a few measures of fear currently available [ 20 ]. Thus, the Scale of Worry for Contagion of COVID-19 (PRE-COVID-19) was recently developed to assess concern about becoming infected with COVID-19 and the impact that this concern may have on people's daily functioning, specifically on their mood and their ability to perform their daily activities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%